Completeness Theorem for Eigenparameter Dependent Dissipative Dirac Operator with General Transfer Conditions. (13th February 2020) - Li, Kun; Zhang, Maozhu; Cai, Jinming; Zheng, Zhaowen
Abstract : This paper deals with a singular (Weyl's limit circle case) non-self-adjoint (dissipative) Dirac operator with eigenparameter dependent boundary condition and finite general transfer conditions. Using the equivalence between Lax-Phillips scattering matrix and Sz.-Nagy-Foiaş characteristic function, the completeness of the eigenfunctions and associated functions of this dissipative operator is discussed.